The market gardener : a successful grower's handbook for small-scale organic farming - Fortier, Jean-Martin (New Society Publishers, 2014)
Les Jardins de la Grelinette is a micro-farm located in eastern Quebec, just north of the American border. Growing on just 1.5 acres, owners Jean-Martin and Maude-Helène feed more than two hundred families through their thriving CSA and seasonal market stands and supply their signature mesclun salad mix to dozens of local establishments. The secret of their success is the low-tech, high-yield production methods they've developed by focusing on growing better rather than growing bigger, making their operation more lucrative and viable in the process. The Market Gardener is a compendium of la Grelinette's proven horticultural techniques and innovative growing methods. This complete guide is packed with practical information on: setting-up a micro-farm by designing biologically intensive cropping systems, all with negligible capital outlay; farming without a tractor and minimizing fossil fuel inputs through the use of the best hand tools, appropriate machinery, and minimum tillage practices; growing mixed vegetables systematically with attention to weed and pest management, crop yields, harvest periods, and pricing approaches. Inspired by the French intensive tradition of maraichage and by iconic American vegetable grower Eliot Coleman, author and farmer Jean-Martin shows by example how to start a market garden and make it both very productive and profitable. Making a living wage farming without big capital outlay or acreages may be closer than you think.